Pengukuran Penerimaan Aplikasi Pengajuan Sertifikat NIK Menggunakan UTAUT dan Social Influence Theory - Faradewi Kirana; Siti Mukaromah; Eristya Maya Safitri (Lembaga Pengembangan Kinerja Dosen, 2024)
The East Java Province Department of Cooperatives and SMEs is taking advantage of advances in technological developments by providing online services. One of the services is, submitting a Cooperative Identification Number Certificate. The problems and difficulties that arise can affect the cooperative's acceptance of the use of the application for a Cooperative Identification Number certificate. For this reason, research was carried out entitled Measuring the Acceptance of Applications for Submitting NIK Certificates Using UTAUT and Social Influence Theory. The choice of UTAUT and Social Influence Theory as conceptual models was based on previous research conducted by Lim et al. (2023). The testing in this research used the SEM-PLS technique and was tested on SmartPLS 4 software. The research results showed that the performance expectancy and subjective norms variables had a significant positive effect on behavioral intention and the electric word of mouth variable had a positive effect on subjective norms and perceived risk. Through this research, insight into user acceptance of the NIK Certificate Submission Application can be understood as an evaluation for improving and improving services in the future.